Alocação de áreas de espera em uma rede de filas com serviços gerais e servidores múltiplos - Gabriel Bahia Caldas (2012)
In this dissertation, results are presented of an empirical analysis of analgorithm proposed in the literature for buffer allocation in finite open acyclic general-service multi-server queueing networks. From the computational results, we conclude that the processing time of the algorithm depends on the number of servers of the network (as expected) but it is independent of the squared coefficient of variation of service time. We also conclude that the allocations obtained are robust and that the approximations for the performance measures are accurate, as attested by simulation. Finally, we conclude that it is not easy to find heuristic rules, such as this multiple server must take that place in the topology, before applying a buffer allocation algorithm to determine which configuration is best.